#TITLE_ALTERNATIVE# - ANGGRAINI , RITA
In this work the catalytic activity of the ions of the transition elements, especially the first period of the transition elements in the periodic system, was studied through the kinetics of the decomposition of hydrogen peroxide in an homogeneous system. By measuring the kinetics of the reaction at the same peroxide concentration, it was found that the rate of the decomposition is dependent on the kind of the catalyst used as well as the hydrogen ion concentration. The other results are obtained from measuring the various levels of peroxide concentration, provided that the rate is first-order to the peroxide concentration. It will be shown that the results from the M2+ ion catalysis can be described by the general relation: [Formula, please click on the file to see the formula] this means the reaction has verified the chain reaction as proposed by Haber and Weiss (1). On the other hand, the results from the M+³ catalysis cannot be described by the same equation, therefore, it is assumed that it follows a different mechanism. The other purpose of this study is to see the possibility of the application of the crystal field theory to explain the catalytic activity of the transition ion. This theory will be applied to the M+n-M+m ion-pair formed during the catalysis.